2019
DOI: 10.1017/s0033291719002393
|View full text |Cite
|
Sign up to set email alerts
|

LSD acutely impairs working memory, executive functions, and cognitive flexibility, but not risk-based decision-making

Abstract: BackgroundPsychiatric and neurodegenerative illnesses are characterized by cognitive impairments, in particular deficits in working memory, decision-making, and executive functions including cognitive flexibility. However, the neuropharmacology of these cognitive functions is poorly understood. The serotonin (5-HT) 2A receptor might be a promising candidate for the modulation of cognitive processes. However, pharmacological studies investigating the role of this receptor system in humans are rare. Recent evide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 69 publications
(102 reference statements)
7
64
1
Order By: Relevance
“…It is therefore conceivable that these changes in brain activity during social decision-making are modulated via dopamine rather than 5-HT systems, in particular since previous results have implicated the dopamine system in decision-making processes 51 . Our results are also in line with previous findings showing that decision-making is a cognitive domain not influenced by stimulating the 5-HT 2A receptor 52 . Therefore, social feedback processing and socially influenced decision-making are potentially modulated by two different neurotransmitter systems, i.e.…”
Section: Social Feedback Processing May Depend On the 5-ht 2a Receptosupporting
confidence: 93%
“…It is therefore conceivable that these changes in brain activity during social decision-making are modulated via dopamine rather than 5-HT systems, in particular since previous results have implicated the dopamine system in decision-making processes 51 . Our results are also in line with previous findings showing that decision-making is a cognitive domain not influenced by stimulating the 5-HT 2A receptor 52 . Therefore, social feedback processing and socially influenced decision-making are potentially modulated by two different neurotransmitter systems, i.e.…”
Section: Social Feedback Processing May Depend On the 5-ht 2a Receptosupporting
confidence: 93%
“…Further, consistent with the notion that psilocybin impairs cognitive focus and control, 5-HT2A agonism has been implicated in an acute decline in convergent thinking, which critically relies on adequate executive functioning (137). In line with this, it was shown that LSD-induced impairment of working memory, executive functions, and cognitive flexibility was mediated by the 5-HT2A receptor (174). Conversely, 5-HT2A agonism is also associated with increased cognitive flexibility and divergent thinking (106,119,127,137,144,175).…”
Section: Executive Functioningsupporting
confidence: 53%
“…It is as yet unclear whether psychedelic microdosing is of therapeutic value for depression due to the limited amount of studies (with small sample sizes) that have been conducted. Nonetheless, the aforementioned effects on selective cognitive processes, resembling in a milder way the effects of full psychedelic doses, 51 , 52 and without impairing cognitive processes, 47 suggest that low doses of psychedelics could play a role in depression. Some underlying cognitive mechanisms of action, deduced from the observed effects, that is, increased divergent thinking and slowed down time perception, could be the induction of respectively increased cognitive flexibility, 31 , 32 and the production of a heightened experience of ‘being more in the present’ or mindful, 33 , 53 which could lead to lessened ruminative thinking and more self-compassion, decreasing depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The latter two were assessed with tasks sensitive to the effects of full psychedelic doses of a psychedelic. 46,47 While no persisting effects on mood were shown 2 days after administration, it has to be noted that this questionnaire was completed by only 55% of the participants. 37 A low LSD dose led to a statistically significant, though clinically irrelevant, increase in systolic (13, 26 mcg) and diastolic (26 mcg) blood pressure 2 h after LSD administration, compared with placebo.…”
Section: Older Research With Lsdmentioning
confidence: 96%